Working and Caring at Home: Gender Differences in the Effects of Covid-19 on Paid and Unpaid Labor in Australia. Issue 1 (3rd April 2021) - Craig, Lyn; Churchill, Brendan
Abstract : The COVID-19 pandemic caused working from home to spike abruptly, creating a unique spatial organization of paid and unpaid work that was not so different for women and men. This paper reports early results from a survey of Australian men and women, conducted during state-imposed lockdown in May 2020, on how the pandemic affected paid work, domestic work, and caring responsibilities. Findings reveal a rise in domestic work burdens for all. Women shouldered most of the extra unpaid workload, but men's childcare time increased more in relative terms, so average gender gaps narrowed. The relative gap in housework remained. While the lockdown generated lower subjective time pressure, dissatisfaction with balance of paid and unpaid work rose markedly and from a much higher base for women. Overall, the results reflect a need for sustained policy attention to the care economy to narrow rather than widen gender disparity. HIGHLIGHTS Lockdowns created extra unpaid work, at the same time as people also worked from home. Men pitched in more, but only to about the same amount as women were doing before the pandemic. Employers expected their workers to be as productive as before the pandemic, ignoring care burdens. Childcare and school closures disproportionally affected women's paid and unpaid work. Women's economic security will be at growing risk unless affordable care services are available.